Asasif, Ägypten. Neues aus dem Grab des Ibi (TT 36) im Asasif auf dem thebanischen Westufer – Die Sargkammer des Psametik und die beiden Sarkophage des Ibi. Die Arbeiten der Jahre 2015 bis 2018 - Wagner, Mareike (e-Forschungsberichte des DAI, 2018)
The research project focuses on the sarcophagus chamber of a man called Psametik, who was buried in the tomb of Ibi in the Asasif, a part of the Theban Necropolis on the westbank of the modern city of Luxor / Upper Egypt, and the two anthropoid sarcophagi of Ibi himself. The sarcophagus chamber of Psametik was discovered in 1989 during the excavation of three shafts in the northern part of Ibi’s tomb. The chamber is decorated with well-preserved images and inscriptions. The two sarcophagi were found in situ within the burial chamber during the excavation in the 1970s. Apart from the well-preserved lid of the inner sarcophagus, which is now in the Museo Egizio in Turin, all other parts are badly damaged and in a fragmented condition.